Oscillatory and Asymptotic Behavior of Second Order Neutral Difference Equations with Maxima - Arul, R.; Angayarkanni, M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we deal with the oscillatory and asymptotic behavior of second order neutral diï¬€erence equations with maxima of the form† (anâˆ† (xn + pnxnâˆ’k)) + qn max [nâˆ’m,n]Â xÂ Î±Â s = 0, n âˆˆ N(n0).Â Example are given to illustrate the main result.